A Sharia Economic Law Analysis of the Sale and Purchase of Shared Premium Canva Accounts - Sholehoddin Sholehoddin; Nurul Imamah (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
This study aims to analyze the practice of buying and selling shared Canva Premium accounts from the perspective of Sharia Economic Law. The increasing demand for digital design tools has led to the emergence of account-sharing transactions, where premium access is resold by third-party sellers at lower prices. Although economically attractive, this practice raises legal and Sharia concerns related to contractual compliance, ownership of digital access rights, and the continuity of benefits.This research employs a qualitative approach using normative analysis of Islamic commercial law (fiqh muamalah) combined with an examination of digital transaction practices. The data were analyzed based on the principles of Sharia Economic Law, particularly the concepts of milk al-manfa'ah (ownership of benefits), gharar (uncertainty), darar (harm), and al-wafa' bi al-'aqd (fulfillment of contractual obligations).The findings indicate that shared Canva Premium account transactions may conceptually be understood as the transfer of digital benefits. However, such transactions are considered problematic due to contractual violations of platform terms, uncertainty regarding access continuity, and the risk of account suspension. These conditions introduce elements of gharar and potential harm, which undermine the validity of the transaction under Sharia principles.This study contributes to the development of contemporary Islamic commercial jurisprudence by highlighting the legal implications of digital subscription-based services. It also provides a critical perspective on the application of Sharia principles in evaluating modern digital economic practices.